2015
DOI: 10.1136/jmedgenet-2015-103076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofMLH1constitutional epimutations as a cause of Lynch syndrome in unselected versus selected consecutive series of patients with colorectal cancer

Abstract: Our results suggest a negligible prevalence of MLH1 constitutional epimutations in unselected cases of CRC. Therefore, MLH1 constitutional epimutation analysis should be conducted only for patients who fulfil the rBG and who lack MLH1 expression with methylated MLH1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 14 publications
2
30
0
1
Order By: Relevance
“…Epimutation was first reported in 2002 in a case of colorectal cancer by Gazzoli et al, based on methylation in a single allele of the MLH1 promoter in peripheral blood DNA [9]. Multiple cases of epimutation in MMR genes have subsequently been described [10,11,12,13,14,15,16,17,18,19]. Based on these cases, the NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) suggest additional tests for epimutation in some cases of colorectal cancers [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Epimutation was first reported in 2002 in a case of colorectal cancer by Gazzoli et al, based on methylation in a single allele of the MLH1 promoter in peripheral blood DNA [9]. Multiple cases of epimutation in MMR genes have subsequently been described [10,11,12,13,14,15,16,17,18,19]. Based on these cases, the NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) suggest additional tests for epimutation in some cases of colorectal cancers [26].…”
Section: Discussionmentioning
confidence: 99%
“…Mangold et al found germline mutations of MLH1 or MSH2 in 62% of patients who fulfilled the revised Bethesda guidelines and had MSI-H [28]. Colorectal cancer patients with suspected Lynch syndrome, who were selected for epimutation tests because of negative germline tests for MMR genes, had MSI and IHC loss of MLH1 due to epimutation at rates of 3%–10% [11,13,14,16,17,29,30,31,32,33]. The current study suggests that similar findings may occur in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations